The Effect of Using a Health Chatbot for Diabetes Consultation on Patient Satisfaction and Lifestyle Management - Elvira Fitriyanti (Al Makki Publisher, 2026)
This study aims to analyze the effect of health chatbot usage on patient satisfaction and lifestyle management in type 2 diabetes patients. The background of the study is based on the increasing prevalence of diabetes in Indonesia and the limited medical personnel, which cause patients to not always receive continuous support. Health chatbots are seen as an innovative solution based on artificial intelligence (AI) that can provide information, education, and reminders interactively. The research method used a quantitative approach with an explanatory survey design involving 220 respondents with type 2 diabetes in urban areas of Indonesia. Data were collected through a Likert-scale-based questionnaire, semi-structured interviews, and observations of patient interactions in digital health communities. Analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationship between variables. The results showed that chatbot usage had a significant positive effect on patient satisfaction (β=0.338, p<0.001) and lifestyle management (β=0.206, p<0.01). Patient satisfaction also significantly influenced lifestyle management (β=0.285, p<0.001) and partially mediated the effect of chatbots on lifestyle (β=0.097, 95% CI [0.043–0.165]). These findings confirm that health chatbots have the potential to become an integral part of digital healthcare services, although their impact on patient physical activity is still limited.